Development of powerefficient and environmentally safe coffee product technologies - Burdo, Oleg; Bezbakh, Igor; Zykov, Aleksandr; Terziev, Sergey; Gavrilov, Aleksander; Sirotyuk, Ilya; Mazurenko, Igor; Li, Yunbo (Eastern-European Journal of Enterprise Technologies, 2020)
Based on the energy and environmental audit, analysis of material flows, energy conversion, emissions into atmosphere and lithosphere in the production of instant coffee was carried out. To raise energy efficiency and reduce environmental burden, innovative flow diagrams and equipment for waste processing and production of new coffee products have been developed. Experimental modeling was carried out: kinetics of microwave extraction of water-soluble substances and oil from coffee slurry; hydraulics of the extractant flow through cassettes of the microwave extractor. The experimental data were summarized in the form of a criterion equation. As a result of experimental modeling of the extraction kinetics, it was found that the duration of the process in a microwave field is approximately 20 times less than in a thermostat. The microwave field affects the extraction rate to a greater extent than the process temperature. The growth of microwave power results in a more than the two-fold rise of the yield of extractives from a coffee slurry. Specification of the microwave oil extractor was defined. The extractor sample was tested at a specific power of 180...240 W/kg in the mode of boiling extractant. Ethanol (93...96 % concentration) was used as an extractant. As a result of the tests, a high-quality coffee oil was obtained. It is characterized by a pronounced aroma, coffee taste and an intense dark brown color. Flow diagram of pre-extraction of coffee from slurry was worked out. Additional extraction of water-soluble extractive substances from coffee slurry increased the extract yield by 10...12 %. The temperature regime of extraction was significantly reduced plus duration and energy intensity of the process were reduced. An innovative flow diagram has been developed for the production of liquid coffee concentrate as a basis for coffee-based drinks ready for immediate use. The concentration of solids is 50...65 %